Integrated Disease Surveillance — Current Need in Vector-Borne Viral Diseases in Nepal - Dumre, Shyam Prakash; Rijal, Komal Raj (Tribhuvan University Journal of Microbiology, 2024)
There has been no systematic study comprised of hospital cases, community (population immunity) and mosquito surveillance to look at the actual dynamics of dengue in Nepal. In fact, there is no data on ZIKA, no molecular data on CHIKV and only single report available on WNV from Nepal. This indicates a huge research gap in mosquito-borne viral diseases in Nepal. Therefore, to understand the full-extent of virus transmission dynamics and potential roles of climate change in virus migration, an integrated virus surveillance system that comprises both human and mosquito component of multiple viruses at a time is essential apart from the classical case-based disease surveillance at hospitals.